Ovicidal Effects of Pineapple Peel Juice (Ananas comosus L.) as a Control of Ascaridians in Chicken (Gallus domesticus) In Vitro - Indira Vania Carisya; Setiawan Koesdarto; Tjuk Imam Restiadi; Nove Hidajati (Journal of Parasite Science (JoPS), 2022)
The aim of this research was to know whether pineapple peel juice can be used as an ovicidal of in vitro A galli. This study used eggs of A. galli worms obtained by collecting adult A. galli worms from the small intestines of fresh local chickens purchased from traditional markets in Surabaya. The research design used was a completely randomized design (CRD) with four treatments , the concentration of pineapple peel juice was 0% (Control), 5%, 10%, and 20%. Each treatment consisted of six replications, with observations on days 5, 10, 15 and 20. Developed eggs were identified with the presence of larvae within egg and the movement of larvae. The data obtained will be analyzed with the ANOVA Statistical Test with the SPSS device and then followed by the Duncan test. The results of statistical analysis showed that pineapple peel juice had a significant effect on the development of A. galli worm eggs In Vitro. The number of damaged A.galli eggs increased as they were given higher pineapple juice concentration. This proves that pineapple peel juice has higher anthelmintic effect with increasing concentration given. Pineapple peel juice 20% is the best juice concentration.